IMMU-41. VERSATILE MRNA-NANOPARTICLE PLATFORM TO REPROGRAM THE BRAIN TUMOR MICROENVIRONMENT AND PREDICT TREATMENT OUTCOME. (14th November 2022) - Grippin, Adam; Mendez-Gomez, Hector; Wummer, Brandon; Weidert, Frances; Wildes, Tyler; Dyson, Kyle; Dobson, Jon; Mitchell, Duane; Sayour, Elias
Abstract: RNA vaccines have shown great promise as activators of immune responses against viral pathogens but their efficacy in cancer is unclear. Here, we describe a versatile, personalized mRNA-nanoparticle (RNA-NP) platform that can be customized to produce powerful anti-tumor immune activation, reprogram the brain tumor microenvironment, and predict vaccine efficacy just two days after treatment. Lipid mixtures (i.e. DOTAP, Cholesterol) with or without iron oxide nanoparticle-cores were complexed with mRNA encoding tumor antigens. Intravenous administration of RNA-NPs induced robust activation of innate immune cells resulting in prolonged survival in murine models of subcutaneous and intracranial melanoma. Inclusion of cholesterol in the lipid backbone enabled delivery of nucleic acids across the blood brain barrier and into tumor-associated myeloid cells in intracranial GL261 and KR158b tumors. These cholesterol-bearing liposomes not only activated innate immune cells in the tumor microenvironment (i.e. increased expression of CD80 and MHCII), but also enabled further manipulation of this compartment. Use of RNA-NPs to deliver siRNA targeting PD-L1 resulted in significant reduction in PD-L1 expression among tumor associated myeloid cells, leading to 37% long term survivorship in combination with systemic checkpoint blockade in an otherwise fatal model of GL261. We have also shown that IONPs incorporated into the cores of these particles enable non-invasive tracking of dendritic cells by MRI, enabling creation of a theranostic approach to: 1) enhance immunologic effects; 2) facilitate translocation across the blood-brain barrier; and 3) enable non-invasive imaging to predict response to RNA-NPs.